2020
DOI: 10.1098/rsta.2020.0009
|View full text |Cite
|
Sign up to set email alerts
|

How might controlled fusion fit into the emerging low-carbon energy system of the mid-twenty-first century?

Abstract: We examine the characteristics that fusion-based generation technologies will need to have if they are to compete in the emerging low-carbon energy system of the mid-twenty-first century. It is likely that the majority of future electric energy demand will be provided by the lowest marginal cost energy technology—which in many regions will be stochastically varying renewable solar and wind electric generation coupled to systems that provide up to a few days of energy storage. Firm low-carbon or zero-carbon res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…This was demonstrated recently at the NIF by Olson et al (2016) and Zylstra et al (2018), where good agreement was observed between experiment and simulation with indirectly driven low-CR wetted-foam capsules. The use of wetted-foam layers is a significant advance, and allows unprecedented levels of control over CR by controlling the initial temperature of the capsule (Walters et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was demonstrated recently at the NIF by Olson et al (2016) and Zylstra et al (2018), where good agreement was observed between experiment and simulation with indirectly driven low-CR wetted-foam capsules. The use of wetted-foam layers is a significant advance, and allows unprecedented levels of control over CR by controlling the initial temperature of the capsule (Walters et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite this success, there is still an important and urgent need for techniques to reduce the energy required to achieve ignition. Tynan & Abdulla (2020) highlighted that the economics of a future low-carbon energy system would likely require that IFE reactors are small (of the order of 100 MW) in order to be economically viable. This will likely necessitate smaller facilities and low drive energies, highlighting the need for techniques to reduce the energy for ignition even in light of this recent result.…”
Section: Introductionmentioning
confidence: 99%
“…In the twenty-first century, gas has grown faster than any other fossil fuel, and renewables are growing even faster today [1]. Failure to recognise this megatrend would be a failure of the energy sector as a whole, and not just a policy error.…”
Section: Introductionmentioning
confidence: 99%
“…Then, in the scholarly article 'How might controlled fusion fit into the emerging low-carbon energy system of the mid-21st century?' [3], George Tynan et al review the current status of electricity demand in the United States and conclude that smaller modular nuclear fusion devices are more likely to fit into existing electricity markets. Nicholas Hawker in his article 'A simplified economic model for inertial fusion' [4] presents results from a 14-variable simulation tool.…”
Section: Introductionmentioning
confidence: 99%